Does gender and social support matter in the associations between loneliness, resilience, and psychological distress? - Koğar Hakan; Yılmaz-Koğar Esin (Psihologija)
In this study, a moderated mediation analysis was conducted to assess whether psychological resilience mediates the association between loneliness and psychological distress and whether this association is moderated by social support or/and gender. So, three different two– and three-way moderated mediation models were tested. The study group of this research consists of 1251 participants from the general population of Turkey. It was determined that loneliness and psychological distress of the group receiving high social support decreased. Resilience shows a partial mediation in the relationship between loneliness and psychological distress. Besides, the relationship between loneliness and resilience is significant. Our study shows that one of the most important variables in reducing psychological distress, regardless of gender, is to reduce loneliness. This study showed that the psychological distress variable, which is one of the most important components in the evaluation of psychological well-being, is directly related to loneliness and resilience variables.